The Effect of Inhalation Smoking by Narghile on Some Parameters Biochemistry - Noor Essam Abdul Rezaq (Journal of Global Pharma Technology, 2018)
The present study included 50 sample collected different of Iraq.25 sample narghile smoker men group and 25 control men group show the results increase significant in MDA, ALT, AST and LDH in narghile smoker men group when compared with control men group , while decrease significant in C.K and ACHE in narghile smoker men group when compared with control men group Keywords: Nargile, Oxidative stress, MDA, LDH , CK , ACHE , ALP , ALT and AST.